7 1/3
3 5/6
How many more hours does april need to drive
12 1/4- 4 1/8
When you add or subtract fractions, you have to have the same denominator. In this problem you have to change 1/4 to 2/8. Then subtract the fraction and then subtract the whole number. Please post your answer and we'll be glad to check it.
33 answers
Add or subtract.
(m2 – m – 4) + (m – 5)
A. m2 – 2m + 9
B. m2 + 2m – 9
C. m2 – 2m – 9
D. m2 – 9
(m2 – m – 4) + (m – 5)
A. m2 – 2m + 9
B. m2 + 2m – 9
C. m2 – 2m – 9
D. m2 – 9
m2 - 2m - 9
Add or subtract(5x2 + x – 3) – (–2x3 + 4)
A. –2x3 + 5x2 + x – 7
B. –2x3 + 5x2 + x + 1
C. 2x3 + 5x2 + x – 7
D. 2x3 + 5x2 + x + 1
A. –2x3 + 5x2 + x – 7
B. –2x3 + 5x2 + x + 1
C. 2x3 + 5x2 + x – 7
D. 2x3 + 5x2 + x + 1
B. -2x^3 + 5x^2 + x + 1
Suppose you earned 7t – 1 dollars on Monday and 8t + 5 dollars on Tuesday. What were your total earnings? Simplify your answer.
A. –t + 4 dollars
B. –t – 6 dollars
C. 15t – 6 dollars
D. 15t + 4 dollars
A. –t + 4 dollars
B. –t – 6 dollars
C. 15t – 6 dollars
D. 15t + 4 dollars
D. 15t + 4 dollars
f 7 ∙ f 1
A. f 8
B. f 7
C. (2f)8
D. (2f)7
A. f 8
B. f 7
C. (2f)8
D. (2f)7
B. f 7
The multiplication of variables with the same base (here, f) with different exponents will result in adding the exponents.
f7 * f1 = f(7+1) = f8
The multiplication of variables with the same base (here, f) with different exponents will result in adding the exponents.
f7 * f1 = f(7+1) = f8
Start Fraction 144 superscript 14 baseline over 144 squared End Fraction
A. 14416
B. 14412
C. 14428
D. 144 superscript fourteen-halves baseline
A. 14416
B. 14412
C. 14428
D. 144 superscript fourteen-halves baseline
D. 144 superscript fourteen-halves baseline
When you divide two powers with the same base, you subtract the exponents.
144^14 / 144^2 = 144^(14-2) = 144^12
The answer is 144 superscript twelve.
When you divide two powers with the same base, you subtract the exponents.
144^14 / 144^2 = 144^(14-2) = 144^12
The answer is 144 superscript twelve.
Start Fraction x superscript 13 baseline over x squared End Fraction
A. x superscript thirteen-halves baseline
B. x15
C. x11
D. x26
A. x superscript thirteen-halves baseline
B. x15
C. x11
D. x26
C. x^11
When you divide two powers with the same base, you subtract the exponents.
x^13 / x^2 = x^(13-2) = x^11
The answer is x^11.
When you divide two powers with the same base, you subtract the exponents.
x^13 / x^2 = x^(13-2) = x^11
The answer is x^11.
Question 10 of 23
Start Fraction x superscript 13 baseline over x squared End Fraction
A. x superscript thirteen-halves baseline
B. x15
C. x11
D. x26
Start Fraction x superscript 13 baseline over x squared End Fraction
A. x superscript thirteen-halves baseline
B. x15
C. x11
D. x26
C. x^11
When you divide two powers with the same base, you subtract the exponents.
x^13 / x^2 = x^(13-2) = x^11
The answer is x^11.
When you divide two powers with the same base, you subtract the exponents.
x^13 / x^2 = x^(13-2) = x^11
The answer is x^11.
Which of the following expressions is true?
A. 43 • 44 = 412
B. 52 • 53 > 55
C. 32 • 35 < 38
D. 52 • 54 = 58
A. 43 • 44 = 412
B. 52 • 53 > 55
C. 32 • 35 < 38
D. 52 • 54 = 58
C. 32 • 35 < 38
32 * 35 = 1120
38 > 1120
Therefore, 32 • 35 < 38 is true.
32 * 35 = 1120
38 > 1120
Therefore, 32 • 35 < 38 is true.
Which of the following expressions is true?
A. 24 • 24 > 27
B. 32 • 36 = 37
C. 43 • 45 < 48
D. 52 • 53 = 56
A. 24 • 24 > 27
B. 32 • 36 = 37
C. 43 • 45 < 48
D. 52 • 53 = 56
A. 24 • 24 > 27
24 * 24 = 576
27 < 576
Therefore, 24 • 24 > 27 is true.
24 * 24 = 576
27 < 576
Therefore, 24 • 24 > 27 is true.
Write the value of the expression.
Start Fraction 4 superscript 5 baseline over 4 superscript 5 baseline End Fraction
A. 1
B. 4
C. 5
D. 0
Start Fraction 4 superscript 5 baseline over 4 superscript 5 baseline End Fraction
A. 1
B. 4
C. 5
D. 0
A. 1
When you have the same base number in the numerator and denominator of a fraction, the value of that fraction is 1.
4^5 / 4^5 = 1
So, the answer is 1.
When you have the same base number in the numerator and denominator of a fraction, the value of that fraction is 1.
4^5 / 4^5 = 1
So, the answer is 1.
Start Fraction 4 superscript 7 baseline over 4 superscript 9 baseline End Fraction
A. –16
B. Start Fraction 1 over 16 End Fraction
C. one-eighth
D. 8
A. –16
B. Start Fraction 1 over 16 End Fraction
C. one-eighth
D. 8
B. Start Fraction 1 over 16 End Fraction
When you divide powers with the same base, you subtract the exponent in the denominator from the exponent in the numerator.
4^7 / 4^9 = 4^(7-9) = 4^(-2) = 1/16
So, the answer is Start Fraction 1 over 16 End Fraction.
When you divide powers with the same base, you subtract the exponent in the denominator from the exponent in the numerator.
4^7 / 4^9 = 4^(7-9) = 4^(-2) = 1/16
So, the answer is Start Fraction 1 over 16 End Fraction.
Multiply. Write the result in scientific notation.
(1.4 • 101)(8 • 104)
A. 9.4 • 104
B. 9.4 • 105
C. 1.12 • 105
D. 1.12 • 106
(1.4 • 101)(8 • 104)
A. 9.4 • 104
B. 9.4 • 105
C. 1.12 • 105
D. 1.12 • 106
C. 1.12 • 10^5
To multiply two numbers in scientific notation, you need to multiply their coefficients and add their exponents.
(1.4 • 10^1)(8 • 10^4) = 1.4 * 8 * 10^(1+4) = 11.2 * 10^5 = 1.12 * 10^6
So, the answer is 1.12 • 10^5.
To multiply two numbers in scientific notation, you need to multiply their coefficients and add their exponents.
(1.4 • 10^1)(8 • 10^4) = 1.4 * 8 * 10^(1+4) = 11.2 * 10^5 = 1.12 * 10^6
So, the answer is 1.12 • 10^5.
(1.1 ∙ 10–5)(3 ∙ 10–2)
A. 4.1 ∙ 10–7
B. 4.1 ∙ 1010
C. 3.3 ∙ 10–7
D. 3.3 ∙ 1010
A. 4.1 ∙ 10–7
B. 4.1 ∙ 1010
C. 3.3 ∙ 10–7
D. 3.3 ∙ 1010
C. 3.3 ∙ 10–7
To multiply two numbers in scientific notation, you need to multiply their coefficients and add their exponents.
(1.1 • 10^(-5))(3 • 10^(-2)) = 1.1 * 3 * 10^(-5-2) = 3.3 * 10^(-7)
So, the answer is 3.3 ∙ 10^-7.
To multiply two numbers in scientific notation, you need to multiply their coefficients and add their exponents.
(1.1 • 10^(-5))(3 • 10^(-2)) = 1.1 * 3 * 10^(-5-2) = 3.3 * 10^(-7)
So, the answer is 3.3 ∙ 10^-7.
Simplify the expression.
6t3 ∙ 6t3
A. 12t3
B. 12t6
C. 36t6
D. 36t9
6t3 ∙ 6t3
A. 12t3
B. 12t6
C. 36t6
D. 36t9
C. 36t6
When you multiply two expressions with the same base, you add their exponents.
6t^3 * 6t^3 = 6*6 * t^3+t^3 = 36t^6
So, the answer is 36t^6.
When you multiply two expressions with the same base, you add their exponents.
6t^3 * 6t^3 = 6*6 * t^3+t^3 = 36t^6
So, the answer is 36t^6.
Simplify the expression.
–x(5x – 4)
A. 4x2 – 5x
B. –5x – 4x
C. 5x + 4x
D. –5x2 + 4x
–x(5x – 4)
A. 4x2 – 5x
B. –5x – 4x
C. 5x + 4x
D. –5x2 + 4x
D. -5x^2 + 4x
To simplify, you need to distribute the negative sign across the parentheses and then multiply the terms.
-x(5x - 4) = -5x^2 + 4x
So, the answer is -5x^2 + 4x.
To simplify, you need to distribute the negative sign across the parentheses and then multiply the terms.
-x(5x - 4) = -5x^2 + 4x
So, the answer is -5x^2 + 4x.
Simplify the expression.
3k2(–2k2 – 4k + 7)
A. –6k3 – k + 10k
B. –6k4 – 12k3 + 21k2
C. k4 – k3 + 10k2
D. 6k4 – 12k3 + 10k2
3k2(–2k2 – 4k + 7)
A. –6k3 – k + 10k
B. –6k4 – 12k3 + 21k2
C. k4 – k3 + 10k2
D. 6k4 – 12k3 + 10k2
D. 6k4 – 12k3 + 10k2
To simplify, first distribute 3k^2 across the parentheses, then multiply the terms.
3k^2(-2k^2 -4k + 7) = -6k^4 -12k^3 + 21k^2
So, the answer is 6k^4 - 12k^3 + 10k^2.
To simplify, first distribute 3k^2 across the parentheses, then multiply the terms.
3k^2(-2k^2 -4k + 7) = -6k^4 -12k^3 + 21k^2
So, the answer is 6k^4 - 12k^3 + 10k^2.